ANALISIS HUMAN CAPITAL TERHADAP PERTUMBUHAN EKONOMI INDONESIA PERIODE 2001 - 2017 - Jojo Jojo; Abel Gandhy; Endang Sari Simanullang; Ana Frasipa (Universitas Tribhuwana Tunggadewi, 2020)
The objective of the present study is to analyze the influence of Government Expenditure on Education and Health, Unemployment Rate, Literacy Rate, to GDP Growth of Indonesian Population. This type of research is quantitative, using ordinary least square method (OLS). The data used are secondary data. Data type is yearly time series data between 2001-2017 period. The results of the study indicate that (1) Government Expenditures for Education and Health have positive and significant impact on the GDP growth of Indonesian Population (2) Unemployment rate has a negative and significant effect on the GDP growth of Indonesian Population (3) Literacy rate positively and significantly to GDP Growth Population Indonesia